Pengaruh Transformational Leadership dan Semangat Kerja Terhadap Kinerja Karyawan di X (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This study was conducted to analyze the influence of transformational leadership and work morale on employee performance at company X, both partially and simultaneously. The study used a quantitative approach with a causal associative design aimed at testing the cause-and-effect relationship between variables. The study population consisted of 37 permanent employees who were also sampled using a total sampling technique, so that the entire population was represented in the study. The main instrument for data collection was a questionnaire using a Likert scale, which allows respondents to provide measurable answers. The collected data were analyzed through multiple linear regression with the help of the SPSS program version 26 to test the influence of each independent variable on the dependent variable. The results showed that the transformational leadership variable obtained an average score of 3.86 which is included in the good category, the work morale variable had an average score of 4.08 also in the good category, and the employee performance variable obtained an average score of 4.17 which is in the good category. Partial regression analysis revealed that transformational leadership has a significant influence on employee performance with a contribution of 40%. Meanwhile, work morale also has a significant influence, although its contribution is smaller at 10%. Simultaneously, both independent variables, transformational leadership and work morale, significantly influenced employee performance, with a combined contribution of 41%. This finding indicates that a transformational leadership style implemented by leaders and high employee work morale can significantly improve performance. However, 59% of other factors outside this study also influence employee performance, such as organizational culture, reward systems, work environment, and intrinsic and extrinsic motivation. Thus, this study emphasizes the importance of implementing transformational leadership and company efforts to improve employee work morale to achieve optimal performance.